2010
DOI: 10.1590/s1677-04202010000300001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methyl Jasmonate on antioxidative enzyme activities and on the contents of ROS and H2O2 in Ricinus communis leaves

Abstract: Jasmonates are a class of plant hormones that mediate various aspects in gene and metabolic regulation, defense, stress responses, reproduction and, possibly, communication. Oxidative stress stimulates synthesis of antioxidant metabolites and enhances antioxidant enzyme activities that could protect plant tissues. The aim of this study was to verify the effects of methyl jasmonate (JAME) treatment on the reactive oxygen species (ROS) and on the activities of H 2 O 2 scavenging enzymes, such as superoxide dismu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 40 publications
3
30
0
5
Order By: Relevance
“…Jasmonates are known to mediate and regulate major stress responses. The role of jasmonates and its derivatives in plants has received considerable attention and various modes of action have been discussed (Farmer and Ryan, 1990;Farmer, 2007;Cao et al, 2009;Soares et al, 2010;Guo et al, 2013;Zhou et al, 2013;Gill et al, 2013). Oxidative stress stimulates synthesis of antioxidant metabolites and enhances antioxidant enzyme activities that could protect plant tissues.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Jasmonates are known to mediate and regulate major stress responses. The role of jasmonates and its derivatives in plants has received considerable attention and various modes of action have been discussed (Farmer and Ryan, 1990;Farmer, 2007;Cao et al, 2009;Soares et al, 2010;Guo et al, 2013;Zhou et al, 2013;Gill et al, 2013). Oxidative stress stimulates synthesis of antioxidant metabolites and enhances antioxidant enzyme activities that could protect plant tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The variations in antioxidant activity within the cell can modify ROS content leading into death or acclimatization response. Soares et al (2010) reported a 33% increase in ROS 1 h after treatment with MeJA in Ricinus communis with decreased activities of CAT and POD in these plants. Accumulation and synthesis of stress-specific defense related protein in Cd-stressed plants are well established (Shah and Dubey, 1998).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations